SUCCESSION PLANNING AS AN ECONOMIC EDUCATION TO IMPROVE FAMILY BUSINESS PERFORMANCE IN EAST JAVA PROVINCE OF INDONESIA - Wahjono, Sentot Imam; Wahjoedi; Idrus, Syafei; Nirbito, J.G. (Econpaper, 2014)
The aim of this paper is to determine the role of succession planning as part of economic education in improving family business performance. Research carried out by using qualitative approach with in-depth interview and outside observation as a technique. The data source is owner of 3 family businesses (6 peoples) as key informants and 6 experts as expertise informants. The data were processed using content analysis. The finding of this research is business start-up from own money and saving and from human capital on entrepreneurship that learn from family; succession planning are necessary but not easy; succession planning conduct after family business growth bigger; succession planning can improve family business performance; economic education in family can make succession planning in family business smoothly. The implication of these finding is need for economic education implemented in the family business, besides the necessary expansion of economic education in society, school and formal level with more focus to the family business.